THE RISK FACTORS IN RELAPSE OF FEBRILE CONVULSIONS - A. F. Dolinina; L. L. Gromova; K. Yu. Mukhin (Эпилепсия и пароксизмальные состояния, 2016)
The factors of risk in relapse of febrile convulsions have been studied: age, sex, perinatal anamnesis, heredity on febrile attacks, epilepsies, neurological status, the results in analysis (EEG, MRI of the head brain), the temperature, the type of the illness, frequency of the illness, the character of febrile paroxysm. 109 children have been investigated aged from three months to five years suffering from febrile attacks. There has been held the comparison of the groups of children with different quantity of episodes of febrile bouts (with one, two, three and more). The results of the observations testify to high degree of credibility the influence of relapsing course of febrile attacks of the following factors: hereditary burden on febrile attacks, the presence of perinatal pathology, frequent acute respiratory diseases.